Uji Stabilitas Fisik Sediaan Lotion Ekstrak Etanol Daun Nangka (Artocarpus heterophyllus Lam.) - Nathalia Halalutu; Jainer Pasca Siampa; Deby Afriani Mpila (Yayasan Bina Lentera Insan, 2026)
Exposure to free radicals such as ultraviolet (UV) radiation could cause skin damage, including premature aging, dryness, and an increased risk of skin cancer. Jackfruit leaves (Artocarpus heterophyllus Lam.) contained secondary metabolites such as flavonoids, tannins, and phenolic compounds with potential as natural antioxidants. This study aimed to determine the physical stability and antioxidant activity of lotion preparations containing ethanol extract of jackfruit leaves. The extraction was carried out using maceration with 96% ethanol, followed by formulation into lotions at concentrations of 2%, 4%, and 6%. Physical stability was evaluated using the freeze-thaw (cycling test) method, including organoleptic, homogeneity, pH, spreadability, and adhesiveness tests. Antioxidant effectiveness was assessed using the DPPH method. The results showed that all formulations met the physical stability requirements. The best antioxidant activity was observed at 4% concentration with an IC₅₀ value of 138.6 ppm. The extract could be formulated into a stable lotion with potential as a topical antioxidant.